A SHARIAH PERSPECTIVE ON ENVIRONMENTAL PUBLIC POLICY MAKING FOR THE ISLAMIC ECONOMIC SYSTEM: EVIDENCE FROM MALAYSIA - Sarabdeen Masahina; A.C. Muhammadu Kijas; Rafia Afroz; Jarita Duasa (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2017)
As a vicegerent of Allah Subhanahu wa taala, human beings are entrusted to pursue revealed teachings, rights, and preserve order and harmony of nature with other forms of life and physical elements. This study investigates the awareness, attitude, and behaviour of households to suggest policies and economic incentives to improve the air quality in Klang Valley, Malaysia. The results show that the level of awareness and attitude towards air pollution is high among the household respondents. However, the behaviour of the respondents is very low. The public policymakers should focus on developing policies to encourage the environmental behaviour of Malaysians. The beliefs of man need to be changed to protect the environment. An Islamic way of life that includes environmental consciousness, simplicity, planning, legislation, monitoring, and resource development are crucial institutions to keep track of developments for environmental public policymaking in the Islamic economic system. ========================================================================================================Kebijakan Publik tentang Lingkungan untuk Sistem Ekonomi Islam dalam Perspektif Syariah: Studi di Malaysia. Sebagai khalifah Allah Subhanahu wa ta'ala, manusia diperkenankan untuk mengikuti wahyu, mengejar hak-hak dan pertapaan yang diwahyukan dan harmoni alam dengan bentuk kehidupan dan elemen fisik lainnya. Studi ini menyelidiki kesadaran, sikap, dan perilaku rumah tangga untuk menyarankan kebijakan dan insentif ekonomi untuk memperbaiki kualitas udara di Klang Valley, Malaysia. Hasil penelitian menunjukkan bahwa tingkat kesadaran dan sikap terhadap polusi udara tinggi di kalangan responden rumah tangga. Namun, perilaku responden sangat rendah. Pembuat kebijakan publik harus fokus pada pengembangan kebijakan untuk mendorong perilaku lingkungan orang Malaysia. Keyakinan manusia perlu diubah untuk melindungi lingkungan. Cara hidup Islami yang mencakup kesadaran lingkungan, kesederhanaan, perencanaan, legislasi, pemantauan dan pengembangan sumber daya merupakan institusi penting untuk melacak perkembangan pembuatan kebijakan publik lingkungan dalam sistem ekonomi Islam.